Apotek Hidup sebagai Solusi Pengobatan Alami di Lingkungan Rumah melalui Pembuatan Jasera Drink - Maulita Saraswati; Yuyun Wahyuningsih; Gillberta Ananda Mulya; Intan Mega Pratiwi; Mely Diah Saputri; Mustafiya Mustafiya; Angga Adhinata; Amalia Kurniasari; Uut Ambarwati (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Indonesia has great potential to utilize medicinal plants through living pharmacies as natural remedies. However, its use at home is still low due to lack of knowledge and a tendency towards synthetic drugs. This activity increases the understanding, awareness, and skills of residents by making JASERA Drink from ginger, lemongrass, and brown sugar. Participatory methods include preparation, observation, education, demonstration, practice, mentoring, and evaluation. Focus on planting ginger, lemongrass, turmeric, galangal and processing hygienic herbal drinks. Results: Community knowledge and skills increased significantly, with high levels of participation and enthusiasm. Living Pharmacies and JASERA Drink are practical, economical, and locally based alternatives. Conclusion: supporting natural home remedies, community health independence, and sustainable medicinal plant conservation.